Integrating Economic and Social Values in the Home Industries: A Study on the Implementation of Creating Shared Value (CSV) in the Gadingrejo Tofu Center - Sinatria, Naufal; Agustina, Fitria Fertha (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the implementation of the Creating Shared Value (CSV) approach in integrating economic and social values within home industries, specifically at the tofu production centre in Gadingrejo. A qualitative approach was employed to investigate the dynamics of collaboration among tofu industry players, farmer groups, local communities, community leaders, and environmental activists in the management of tofu waste into liquid organic fertilizer (LOF). The research findings indicate that cross-sector collaboration can create solutions that not only address environmental pollution issues but also generate economic benefits for local actors. This process forms an interdependent social ecosystem and supports the achievement of several Sustainable Development Goals (SDGs), such as sustainable production, food security, and strategic partnerships. This research implies that CSV in the context of home industries is not merely a business strategy but also a driving force for value-based social change, community independence, and environmental sustainability